2002
DOI: 10.1034/j.1399-3089.2002.1o038.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of xenogeneic MHC class II molecules in HLA‐DR+ and ‐DR cells: influence of retrovirus vector design and cellular context

Abstract: We recently established that molecular chimeras of major histocompatibility complex (MHC) class II molecules, created via retroviral transfer of allogeneic class II cDNAs into bone marrow cells (BMCs), alleviated complications associated with mixed BMC chimeras while leading to T cell tolerance to renal grafts sharing the transferred class II. Initially demonstrated for allogeneic transplants in miniature swine, this concept was extended to T-dependent antibody (Ab) responses to xenogeneic antigens (Ags) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Additional data from our group support the MHCII peptide hypothesis. We observed that human B cell lines, transduced with a pig MHCII DR gene, did not express surface pig DR but stimulated autologous human T cell proliferation, which was only blocked by anti-human MHCII mAbs (41). …”
Section: Discussionmentioning
confidence: 99%
“…Additional data from our group support the MHCII peptide hypothesis. We observed that human B cell lines, transduced with a pig MHCII DR gene, did not express surface pig DR but stimulated autologous human T cell proliferation, which was only blocked by anti-human MHCII mAbs (41). …”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, the Tg product was not expressed at the surface of the manipulated BM cells. This finding was confirmed in vitro by showing that prototypic class II committed cell lines, such as dendritic, B, and endothelial cells, were unable to produce membrane-bound Tg class II heterodimers after transduction (23).…”
Section: Tolerance To Mhc Class Ii-matched Transplantsmentioning
confidence: 67%
“…Further mechanistic studies revealed that class II ϩ B-cell lines transduced by foreign Tg class II cDNA, leading to negative expression of surface Tg molecules, were still able to trigger proliferation of self-CD4 ϩ T cells, strongly suggestive of peptide presentation of the transgenic class II product on B-cell class II heterodimers (23). Antibody-blocking experiments confirmed that the Tg class II-derived peptides were preferentially presented on surface class II molecules of the B cells.…”
Section: Tolerance To Mhc Class Ii-matched Transplantsmentioning
confidence: 91%
“…Nonetheless, foreign class II chains sequestered in transduced APCs appeared to be processed as peptides docked selectively on APC surface class II heterodimers. Indeed, the proliferation of T helper (Th) cells to self-class II þ APCs, transduced with foreign class II, could be blocked by monoclonal antibodies (mAbs) to APC class II, but not to transgenic class II [23]. Because bone-marrow class II þ APCs are instrumental in the induction of T-cell tolerance [24], they might additionally be key participants in regulatory tolerance induction following class II gene therapy.…”
Section: Mechanism Of Class II Matching: a Clue To T-reg-cell-mediatementioning
confidence: 99%